KESADARAN HUKUM DALAM BELA NEGARA DAN CINTA TANAH AIR (NKRI) BAGI PASIEN PROLANIS KLINIK PRATAMA ”RAHMATIKA” SEMARANG - Muzayanah (Jurnal Pengabdian Kepada Masyarakat Media Ganesha FHIS, 2022)
The Republic of Indonesia is an independent, united, sovereign, just and prosperous country. As the Unitary State of the Republic of Indonesia (NKRI), Indonesia is an independent country which was proclaimed on August 17, 1945. As an independent country, the Indonesian state has the right to regulate and administer the state administration system of the Republic of Indonesia based on the state constitution, namely the 1945 Constitution. an independent Indonesian state, it is necessary to pay attention to all Indonesian citizens so that this country continues to develop and progress as aspired in the fourth paragraph of the opening of the 1945 Constitution. Awareness in the nation and state must be realized by carrying out State Defense and love for the homeland in the Unitary State of the Republic of Indonesia. , so that our country remains an independent, just and prosperous country based on Pancasila and the 1945 Constitution. State defense is a form of public awareness to participate in maintaining security in their respective environments according to their capacity and profession. ng each. State defense can be carried out by maintaining the safe situation of each family and carrying out its activities as the smallest community unit in a country. The next question is whether the residents of Prolanis Patients at the "Rahmatika" Primary Clinic in Semarang City in general have known about what is meant by State Defense? And what is meant by the love of the Republic of Indonesia?. It turns out that there are still many residents of Prolanis at the "Rahmatika" Clinic who do not know or even understand what is meant by State Defense. When asked about State Defense, most answered that what was meant by State Defense was a way to deal with the enemy in the event of a war, so it was often understood that they had to take up arms to fight against the enemy. Apart from that, after we as implementers of Community Service activities in the form of legal counseling from Unisbank, we asked them about whether they knew about State Defense? and it turns out that most of them do not know and understand what is meant by Defending the State and Loving the Republic of Indonesia. Based on this fact, we implementer of Community Service activities have a program to provide education about forms of legal awareness in Defending the State and Love for the Homeland of the Republic of Indonesia, so that we hope to be able to foster a sense of love for the homeland and State Defense for an independent Indonesia. Given the very importance of education about State Defense, so that every citizen of the Prolanis Patient at the Pratama Clinic "Rahmatika" knows and understands so that it is hoped that the legal awareness of the community will grow in this State Defense and to make the public more aware of the importance of unity and integrity in social life. , as a nation and state in carrying out State Defense in accordance with their respective professions or expertise.